ANALISIS METODE PENCATATAN PERSEDIAAN AIR MINERAL AQUA PADA UD KALTIM MAKMUR DI KABUPATEN BERAU - Siti Munawaroh (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
A good inventory system can be seen from how an inventory is reported correctly and accurately on the company's balance sheet. In order for this to be achieved, it is necessary again to be precise and precise in terms of recording, appraising and determining the cost of goods. Apart from being very influential in the company's financial statements, this will also affect the supervision of the company's inventory which is indirectly related to the supervision of the company's employees itself.The purpose of this study was to clearly determine the application of the method of recording and assessing the Aqua Mineral Water supply at UD Kaltim Makmur in accordance with PSAK No. 14 concerning Inventory. The analytical method used in writing this thesis is quantitative descriptive analysis.The results of this study concluded that the application of the Aqua Mineral Water supply recording method at UD Kaltim Makmur was not in accordance with PSAK No. 14. The inventory recording method used by UD Kaltim Makmur is the periodic method. The use of the periodic recording method at UD Kaltim Makmur is not in accordance with PSAK No. 14, which should use a perpetual method or with the use of inventory cards. UD Kaltim Makmur calculates the inventory value without using the cost formula required in PSAK No. 14, so the method used by UD Kaltim Makmur is not in accordance with PSAK No. 14.